FEATURES OF BASIC WOOD DENSITY DYNAMICS FOR STEM WOOD OF EUROPEAN SPRUCE IN PREVAILING FOREST SITE TYPES ON THE TERRITORY OF POLONINSKYY RIDGE (UKRAINIAN CARPATHIANS) - Zadorozhnyy, A. I.; Hrynyk, H. H. (Forestry and Forest Melioration, 2018)
Introduction One of the main indices characterizing wood is the basic density of the trunk wood. To study the phytomass of spruce trunk wood it is important to analyze the influence of site type conditions and that of mountain altitude zoning on the basic density dynamics as well as the dependence of this index on taxation indices of the tree (its height and trunk diameter at the height of 1.3 m). The aim of this research is the evaluation of the basic density of spruce trunk wood in secondary spruce forest stands of beech types of site conditions (TSC) С3 (moist fairly fertile) and D3 (moist fertile) types in the territory of Poloninskyy ridge of the Ukrainian Carpathians. Materials and methods To study the density dynamics of trunk phytomass components (trunk wood, the wood of the trunk in bark and trunk bark) of secondary spruce forest stands the data from 28 temporary plots (TP) were used. The test areas were set within the forest funds of the following enterprises: Mizhgirske State Forestry Enterprise (Mizhgirske SFE), Volovetske SFE, Svalyavske SFE of the Transcarpathian Regional Forestry Administration in the territory of Poloninskyy Range of the Ukrainian Carpathians. The ages of the studied forest stands in the test areas vary from 18 to 102 years, their quality class is І–ІІ, and relative thickness is from 0.64 to 0.81. In order to determine the basic density of trunk phytomass components, 437 trunk samples were selected and studied from the total number of 120 model trees. The data obtained as a result of the experimental field work were processed in chambers using Statistica 10 and MS Excel applied programs. Results The values of local density indices were determined on stumps and relative trunk heights of 0.25h, 0.50h, and 0.75h. The studied material was grouped according to the types of forest site conditions, and average values of trunk phytomass components density of spruce trees were determined. The lower values of average density for trunk wood and wood of the trunk in bark in the absolutely dry state were found to be common for the trunk wood in TSC С3 (404 ± 6 and 403 ± 10 kg·(m3)-1, respectively) in comparison with TSC D3 (424 ± 5 and 420 ± 12 kg·(m3)-1). The average density of the trunk bark in TSC D3 is 400 ± 3 kg·(m3)-1 and is lower as compared with TSC С3 (410 ± 8 kg·(m3)-1). The maximum values agree with those of the basic density of the trunk wood, trunk in the bark and trunk bark in TSC С3 (392 ± 9, 391 ± 6 and 406 ± 8 kg·(m3)-1, respectively). In TSC D3, the trunk wood density is 345 ± 8 kg·(m3)-1, the wood density of trunk in the bark is 327 ± 6 kg·(m3)-1, and that of the bark is 303 ± 7 kg·(m3)-1. The maximum difference in the average values of basic density in different types of forest type conditions is characteristic of the bark – 103 kg·(m3)-1 (25,4 % of the value in TSC С3), in comparison with the rest of fractions where this difference is less significant – the value of average basic density of the trunk wood varies within 45 kg·(m3)-1 (12,0 % of the value in TSC С3), while that of the wood of trunk in bark varies within 64 kg·(m3)-1 (16,4 % of the value in TSC С3). Conclusions The higher values of the average basic trunk wood density in spruce are common in the trees in test areas of TSC С3, as compared with D3. Exclusions are the trees of spruce in TSC D3, having trunk diameters of 12–14 cm and 8 m of height. It is evident that the studied samples have been selected from the model trees that were retarded of growth from the rest of the trees in this type of forest site conditions. A characteristic feature of the dynamics of values of average basic trunk wood density in spruce with aging for TSC С3 and D3 is a decrease of the index values in the young age and gradual increase of those towards the maturity age. The average index values are higher in TSC С3, as compared with TSC D3.